Rapid Survey of Endangered Hispid Hare, Caprolagus hispidus in North Bank Landscape, North-East India - Nath, Naba K. (Indian Forester, 2015)
This rapid survey was the first ever attempt to find out the status and distribution of hispid hare in north-east India within the North Bank Landscape which covered nine protected areas within Assam and Arunachal Pradesh. The survey finds out evidence of hispid hare's presence in three of the protected areas i.e., Barnadi Wildlife Sanctuary, Nameri Tiger Reserve and D'Ering Wildlife Sanctuary. A preliminary assessment of grassland habitats within the study sites was conducted using GIS and RS technology. The survey further identifies the potential threats to tall grassland habitats available in all the protected areas including the sites where evidence of hispid hare reported.